Radio Jambi Hingga Menjadi Radio Republik Indonesia (RRI) Jambi Tahun 1957-1975. - Sidik, M. Ja’far; Kaksim, Kaksim; Kharles, Kharles (Pendidikan Sejarah, 2013)
ABSTRACTÂ This thesis is a study of the history of the press by selecting the title of Radio Jambi To Become Radio Republik Indonesia (RRI) Jambi 1957 -1975. It is interesting to discuss, because the presence of the Jambi radio community will know where the information about the state of Indonesia in particular regions of Jambi. The history of RRI Jambi can not remove the existence of radio Jambi, the birth of radio Jambi itself was established by the military and involved jawatan penerangan batanghari Jambi in setting up this radio. With the birth of Jambi province on January 6, 1957, it is the desire of the leaders who want to make the radio RRI Jambi Jambi is the blessing of the center through SK Transitional Council of the Autonomous Regional Government of Jambi No. First Level. UP. 175/1959 dated 26 September 1959. RRI Jambi then officially established and chaired by Mr. Muhammad Nurdin Supomo directly from year 1960 to 1966. Much has changed after 6 years for MN Supomo served as the broadcast hours increased to 8 hours a day, and the infrastructure that has begun to be furnished. After 6 years of MN Supomo served Subsequently he was replaced by Efendi Bactiar 1966 to 1967, not long-serving, Bactiar Efendi was replaced by Anwar Azel 1967-1975. Here Azel Anwar wants to build the main building RRI Jambi aligned with other government agencies, this can be the accomplishment by building a central office area RRI Jambi in Jambi province.Â Â Keywords: Development, Radio Jambi, RRI Jambi